KSTP 94, an open-pollinated maize variety has postattachment resistance to purple witchweed (Striga hermonthica) - Mutinda, S.M.; Masanga, J.; Mutuku, Josiah M.; Runo, S.; Alakonya, A.E. (Cambridge University Press, 2018)
Striga spp. are obligate root hemiparasites that constrain cereal production in sub-Saharan Africa. Although purple witchweed [ Striga hermonthica (Delile) Benth.] and Asiatic witchweed [ Striga asiatica (L.) Kuntze] infect all cereal crops, maize ( Zea mays L.) is particularly vulnerable to their infestations. A sustainable control strategy for Striga would be to breed crops with host-based resistance as part of an integrated management plan. In maize, the open-pollinated variety Kakamega Striga -tolerant population of the year 1994 (‘KSTP 94’) has been popularized as a Striga -tolerant/resistant variety. This resistance was earlier reported to result from production of low amounts of sorgomol, a less potent strigolactone. To determine whether KSTP 94 harbors postattachment resistance, we used a soil-free assay based on observation chambers called rhizotrons. We found that the size of Striga seedlings attached to ‘CML 144’ (a susceptible maize inbred line) were 2.5-fold longer than those on KSTP 94. In addition, KSTP 94 had significantly fewer Striga attachments, which corresponded to significantly lower biomass (2.6-fold) compared with CML 144. Histological analysis revealed that the low Striga growth and development while infecting KSTP 94 was due the parasite’s inability to penetrate the host’s endodermis and make effective xylem–xylem connections. We therefore conclude that in addition to preattachment resistance, KSTP 94 exhibits postattachment resistance to S. hermonthica and could therefore be a good genetic source for postattachment resistance breeding.